Desarrollo e implementación del módulo de matriculación e inscripciones en las carreras de pregrado que integra el Sistema Informático de la Universidad Técnica de Machala (SIUTMACH) - Aguilar Alvarado, Jonathan Víctor (2010)
According to our thorough research conducted at the Technical University of Machala we highlight a number of disadvantages that arise based on the process of enrollment of students.